Combatting Illicit Trade on the EU Border A Comparative Perspective - Nowak, Celina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book provides the first-ever comparative study on criminal policy concerning the illicit trade of tobacco, conducted among four comparatively new EU Member States (Lithuania, Poland, Slovakia and Romania) and two (3z(Bold(3y (BEU countries (Germany and Italy). The book addresses the national legal frameworks, current criminological situation regarding illicit trade of tobacco, and the practical challenges faced by national law enforcement authorities in the countries examined. It also considers the international framework, and concludes with a horizontal report. The objective of the book is to highlight legislative and practical challenges in the fight against illegal tobacco products at the national and transnational level, and to formulate recommendations for overcoming them more effectively in Europe.s
Part I: Introduction -- Introduction: Fighting Against Illicit Tobacco Trade in the Era of Fast Change -- International Legal Framework on the Fight Against Illicit Tobacco Trade: An Overview -- Part II: Criminal Policy with Regard to Illicit Tobacco Trade: National Experiences and Challenges -- Between Taxes, Criminal Law and Health Care: The Fight Against Illicit Tobacco Trade in Germany -- The Italian National Legal Framework Related to Illicit Trade in Tobacco Products -- Prevention of Illicit Trade in Tobacco Products: Experience of Lithuania -- Legal and Practical Challenges of Combating Illicit Trade of Tobacco in Poland -- A Complex Legal Framework for a Lack of Legal Certainty: Case Study of Romania -- Prevention and Repression of Illicit Trade in Tobacco Products: Experience of Slovakia -- Part III: Conclusions -- Conclusions: Criminal Policy on Illicit Tobacco Trade Between Scylla of Health Concerns and Charybdis of Fiscal Interests.
Keywords: Commercial law; European Economic Community; Private international law; Conflict of laws; International law; Comparative law; Trade regulation; European Economic Law; Private International Law, International and Foreign Law, Comparative Law; International Economic Law, Trade Law